Novas estratégias terapêuticas para o tratamento da leucemia mieloide aguda (LMA): PJOV56, um agente causador de dano de DNA e uma combinação terapêutica entre um inibidor de RNA Pol I (CX- 5461) e um inibidor de CDKs (Dinaciclib) - Maranhão, Sarah Sant'Anna (2020)
Acute myeloid leukemia (AML) is the malignant hematologic disease most common in adults characterized by clonal proliferation of immature myeloid cells in the peripheral blood, bone marrow and other tissues. Treatment for AML has been less than optimal with little changes in the standard induction regimen (anthracycline and cytarabine) over the past 40 years. AML treatment landscape has been changing with new therapies emerging in recent years, however such progress remains unsatisfactory with a low survival rate. Therefore, the constant search for new therapies or drug combinations that can assist AML treatment. In this thesis, we present two new approaches to treat AML. The first consists of a small synthetic quinoxaline synthesized in Brazil. In previous studies, PJOV56 showed an antineoplastic potential by inducing autophagy in colorectal cancer cells (HCT-116). In the present study, PJOV56 exhibited better cytotoxic activity in AML cell lines, inducing DNA damage in KG1 cells. The activation of DNA damage response pathways included phosphorylation of H2AX, CHK1 and CHK2 with consequent cell cycle arrest in G0/G1 and S phases, triggering apoptotic process. PJOV56 also showed safety with reduced genotoxicity in healthy cells (inducing micronucleus formation and DNA damage only at concentrations thirty times higher than the tumor cells IC50 values). In addition, the molecule did not induced toxicity in C57BL/6 healthy mice. The second treatment proposed consists of a combination therapy between and RNA Pol I inihibitor (CX- 5461) and an CDKs inhibitor (Dinaciclib). Combination therapy, previously tested in a syngeneic AML mouse model that predicts human response MLL/ENL Nras p53WT, led to a survival benefit indicative of a synergistic effect. Here the molecular mechanism underlying this phenomenon was evidenced in vivo by drugs target inhibition, triggering of apoptotic process with capase 3 and PARP cleavage and phosphatidylserine externalization and cell cycle arrest. Along with the combination therapeutic efficacy was proven in another AML mouse model beyond a MLL rearrangement, AML1/ETO9 Nras p53WT. Thus, this thesis suggests two new therapeutic approaches to potentially treat AML.